2022
DOI: 10.3389/fnbeh.2022.968889
|View full text |Cite
|
Sign up to set email alerts
|

The implications of alcohol mixed with energy drinks from medical and socio-legal standpoints

Abstract: Co-ingestion of energy drinks and alcohol has long been in practice and has been poorly regulated despite a growing body of literature of their potential negative health impacts. Co-ingestion of energy drinks with alcohol has multiple counter-active effects such as reduction of body sway, fatigue and sedative effects induced by alcohol, along with increased subjective feeling of alertness, which may lead to increased binge-drinking, intoxication, decreased perception of intoxication, dehydration, and alcohol p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Alcohol mixed with energy drinks (AMED) results in various opposing effects including diminished body sway, fatigue, and sedation caused by alcohol, coupled with heightened subjective alertness. This combination may contribute to elevated instances of binge-drinking, intoxication, reduced awareness of intoxication, dehydration, and the risk of alcohol poisoning 33 . Some studies found also an association between ED consumption and the habit of smoking 1 , 15 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol mixed with energy drinks (AMED) results in various opposing effects including diminished body sway, fatigue, and sedation caused by alcohol, coupled with heightened subjective alertness. This combination may contribute to elevated instances of binge-drinking, intoxication, reduced awareness of intoxication, dehydration, and the risk of alcohol poisoning 33 . Some studies found also an association between ED consumption and the habit of smoking 1 , 15 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Combining alcohol with energy drinks is a highly popular practice among young adults and adolescents. Although it is not fully understood why these age groups are so inclined towards this combination, some literature suggests that it may be related to improving the taste of alcohol and seeking an additional source of energy [50]. It has been demonstrated that consuming energy drinks with alcohol enhances the euphoric effects of the alcohol, acts as a stimulant, prolongs the drinking session, and also increases the likelihood of developing the alcohol use disorder (AUD) [51].…”
Section: State Of Knowledgementioning
confidence: 99%
“…Another very common practice among teenagers is to consume a mixture of energy drinks and alcohol, the mixture of which causes, among other changes, a false subjective sensation of alertness, which can lead to increased alcohol consumption and increase the harmful effects on the body 36,37 .…”
Section: Effects Of Alcohol On Social Relationshipsmentioning
confidence: 99%